Impacto de los programas sociales en la disminución de la pobreza - Quispe Quispe, Milagros Rosario (2017)
In Peru, in the period 2009-2015, both monetary poverty and extreme monetary poverty at the national level have declined, however, rural poverty levels are still very high, poverty is higher in the sierra than in the jungle and the coast at rural area. Likewise, rural populations are the ones that have benefited least from Peru's economic growth in this period, mainly the population living in the highlands. On the other hand, extreme poverty or extreme poverty affects almost exclusively the rural population of the sierra and the jungle. On the other hand, one of the main problems facing social programs in Peru is the targeting, which generates the problem of leakage and undercoverage, which in turn generates an increase in social costs. During the review period, the budget for these programs has increased while progress in reducing poverty levels has not been very significant, as the reduction has been declining.